Rhodium-Catalyzed C–C Bond Olefination of Ring-Fused Benzocyclobutenols and Application in the Construction of Polycyclic Compounds - Mao, Wenbin; Zhu, Chen (Synlett, 2018)
A novel rhodium-catalyzed C–C bond olefination of ring-fused benzocyclobutenols with ethyl acrylate is described. A variety of versatile olefinated products were efficiently generated at room temperature and then readily converted into many useful polycyclic compounds by one-step processes. The reaction provides a practical C–C bond olefination method with high atom efficiency.
Keywords: rhodium catalysis; olefination; polycyclic compounds; atom efficiency; benzocyclobutenols